Exploration of safe space for traumatic urban youths amidst urban growth - Hui Yen, Kok; Mohd Noor, Mohd Zairul; Lawrence D’silva, Jeffrey (Human Resource Management Academic Research Society, 2023)
For traumatised urban youths, a youth safe space can simply be access to refuge, a place where they feel safe and protected as well as being comfortable in their own skin. Youth require secure public areas where they can congregate, participate in activities that cater to their wide range of needs and interests, influence decisions, and express themselves freely. However, there is no specific design or guideline for trauma-oriented design to create a safe space for traumatic urban youths. Therefore, this research will formulate trauma-oriented design approaches that creates a safe space for urban youths. A literature review was carried out using various databases to explore solutions to the questions posed in the study. The study shows a safe space in rehabilitation design framework for traumatic urban youths in urban areas. Besides, this study identifies the needs of the traumatic community and trauma-oriented design in community-based rehabilitation that will help the community cope with the stresses in life and work productively. Future research can conduct qualitative study to look in-depth on the interface between community-based rehabilitation and trauma-oriented design in a safe space.